Demographics of sustainable technology consumption in an emerging market: the significance of education to energy efficient appliance adoption. Issue 6 (10th May 2019) - Nguyen, Ninh; Greenland, Steven; Lobo, Antonio; Nguyen, Hoang Viet
Abstract : Purpose: This paper aims to address gaps in the sustainable technology literature by evaluating the demographics of energy efficient appliance consumption in Vietnam. Sustainable technologies can reduce greenhouse gas emissions and address environmental problems such as air quality and climate change. Opportunity is the greatest in emerging markets, where population growth has triggered dramatic rises in electricity consumption. However, their adoption of energy efficient appliances has been slow and understanding why is limited. Design/methodology/approach: Following a literature review, a questionnaire was designed to capture sustainable consumption attitudes and behaviours. In total, 682 interviews were conducted among Vietnamese electrical appliance consumers to investigate the influence of demographics on sustainable technology consumption. Findings: While many respondents were aware of the sustainable benefits of energy efficient appliances, this did not generally translate into responsible purchase behaviour. Of the demographic variables, education had the strongest relationship with sustainability. Those with higher incomes and more children were also more likely to exhibit sustainable consumption attitudes and behaviours. Gender and age were weaker sustainability predictors. Originality/value: This study is relevant to a wide range of sustainable technology contexts. The literature shows contrary findings regarding relationships between demographics and sustainable consumption, and the value of demographics to sustainable consumer segmentation and targeted behaviour change campaigns has been contested by some researchers. This research highlights education as the most significant demographic predictor of sustainable consumption and reveals the consistency of this finding with many other studies. The implications of this for promoting future sustainability are discussed.